Place, identity and material culture: Pulperías and supermarkets as landmarks - Bolaños Carpio, Alexa (2021)
Received: 04-01-2021. Approved: 18-03-2021. This article examines the pulperías (i.e., small grocery stores) and supermarkets as landmarks in the Cosa Rican addresses, and aims to show their identity with the communities. This study is a qualitative research, and the data come from telephone call recordings to 9-1-1 Emergency Service in Costa Rica. Findings show that pulperías and supermarkets are objects of material culture and are part of the everyday material environment of people, as they reveal identity aspects that evidence changes in society. Pulperías show the community life and daily small purchases, whereas supermarkets show the change in consumption habits on a large scale in the community and the different interactions with the people who work there. Finally, pulperías become landmarks due to the processes of cultural meaning, frequency of encounter and prominence, whereas supermarkets become landmarks due to the processes of large immobile objects and frequency of encounter.